Competitiveness and Economic Growth of 5 ASEAN Countries - Marselina; I Wayan Suparta; Fadeli Yusuf Afif (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
This study aims to analyze the state competitiveness condition of the Corruption Perception Index, political risks, and Foreign Direct Investment and their effects on ASEAN economic growth. The data used is panel data consisting of time series data for 2009 - 2019 and cross sections of five ASEAN developing countries with the highest level of competitiveness, namely Malaysia, Indonesia, the Philippines, Thailand and Vietnam. The variables used are economic growth, competitiveness, Corruption Perception Index, political risk, and Foreign Direct Investment. The analysis tool used is panel data regression, the Fixed Effect Model (FEM). The results showed that competitiveness, Corruption Perception Index, political risk, and Foreign Direct Investment had a positive and significant effect on the economic growth of the five ASEAN countries in 2009-2019. In an effort to increase the country's daylight power, of the 12 pillars, Indonesia, Vietnam and the Philippines are superior in market value that are ranked 7th, 26th and 31st. Malaysia and Thailand are superior in financial system values which are ranked 15th and 16th This shows that there is a need to improve the other pillars to encourage increased daytime power and can increase a country's economic growth.